2014
DOI: 10.1073/pnas.1405621111
|View full text |Cite
|
Sign up to set email alerts
|

EARLY BUD-BREAK 1 (EBB1) is a regulator of release from seasonal dormancy in poplar trees

Abstract: Trees from temperate latitudes transition between growth and dormancy to survive dehydration and freezing stress during winter months. We used activation tagging to isolate a dominant mutation affecting release from dormancy and identified the corresponding gene EARLY BUD-BREAK 1 (EBB1). We demonstrate through positioning of the tag, expression analysis, and retransformation experiments that EBB1 encodes a putative APETALA2/Ethylene responsive factor transcription factor. Transgenic up-regulation of the gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 53 publications
8
119
0
Order By: Relevance
“…Our data suggest that transient reduction in symplasmic connectivity and sink activity at the apex of the main stem may contribute to sylleptic branching from young AXBs that are still sinks. What the possible connection is between GH17_44 and the cytokinin-induced gene EARLY-BUD BREAK1 ( EBB1 ), overexpression of which induces somewhat similar sylleptic branches in P. deltoides (Yordanov et al , 2014), remains to be established. It is tempting to speculate that EBB1-like proteins act in the wake of GA-inducible 1,3-β-glucanases that re-functionalize symplasmic input conduits.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that transient reduction in symplasmic connectivity and sink activity at the apex of the main stem may contribute to sylleptic branching from young AXBs that are still sinks. What the possible connection is between GH17_44 and the cytokinin-induced gene EARLY-BUD BREAK1 ( EBB1 ), overexpression of which induces somewhat similar sylleptic branches in P. deltoides (Yordanov et al , 2014), remains to be established. It is tempting to speculate that EBB1-like proteins act in the wake of GA-inducible 1,3-β-glucanases that re-functionalize symplasmic input conduits.…”
Section: Discussionmentioning
confidence: 99%
“…EBB1, a member of the ERF family of transcription factors, has been identified recently by Yordanov et al . () as a gene that may participate in bud burst in poplar, by screening a population of activation‐tagged hybrid poplar lines for early bud burst. EBB1 overexpressors displayed early bud burst, whereas the downregulation of EBB1 resulted in delayed bud burst and changes in the expression of genes associated with various metabolic processes, meristem growth and regulation of hormone levels (Yordanov et al ., ).…”
Section: Establishment and Release Of Bud Dormancymentioning
confidence: 99%
“…A role of hormones, particularly abscisic acid (ABA) has been well established in both bud and seed dormancy (Rohde and Bhalerao, 2007; Horvath et al, 2008; Graeber et al, 2012) and commonalities in genes that regulate bud and seed dormancy were reported in peach (Leida et al, 2012a; Wang et al, 2016). A novel regulator, putative APETALA2/Ethylene responsive transcription factor EARLY BUD-BREAK 1 ( EBB1 ) was also identified as a determinant of the time of bud break in Populus (Yordanov et al, 2014) and subsequently associated with bud break regulation in apple (Wisniewski et al, 2015). Ectopic expression of a peach C-repeat binding factor (CBF/DREB) gene PpCBF1 in apple resulted in unexpected short-day induced dormancy and delayed budbreak in spring (Wisniewski et al, 2011; Artlip et al, 2014), demonstrating a role of a cold-tolerance gene in regulation of growth and dormancy in trees.…”
Section: Introductionmentioning
confidence: 99%